1993
DOI: 10.1159/000239112
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Activity of Levofloxacin, Ofloxacin and Other Quinolones against Coagulase-Negative Staphylococci

Abstract: The in vitro activity of levofloxacin against coagulase-negative staphylococci (CNS) was investigated. In vitro, on the basis of MIC90 values, levofloxacin was as active as ciprofloxacin, inhibiting both methicillin-sensitive and -resistant staphylococci at 0.5 μg/ml. The frequency of one-step development of levoflox-acin-resistant CNS was < 1 x 10––9. After repeated transfer of CNS in the presence of increasing concentrations of levofloxacin or other quinolones, there were 4-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

1994
1994
1998
1998

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 4 publications
2
4
0
Order By: Relevance
“…For Stenotrophomonas maltophilia isolates and gram-positive cocci, the MICs of these two drugs were comparable, but because of the twofold higher susceptibility breakpoint of levofloxacin, greater percentages of these organisms were susceptible to levofloxacin. These data are consistent with previously published results (3,5,8,10,12,17,22,25). Despite the greater in vitro activity of ciprofloxacin against P. aeruginosa isolates and the Enterobacteriaceae, levofloxacin has proved to be more effective than ciprofloxacin in treating experimental infections in rats in one study (16).…”
Section: Methodssupporting
confidence: 91%
See 1 more Smart Citation
“…For Stenotrophomonas maltophilia isolates and gram-positive cocci, the MICs of these two drugs were comparable, but because of the twofold higher susceptibility breakpoint of levofloxacin, greater percentages of these organisms were susceptible to levofloxacin. These data are consistent with previously published results (3,5,8,10,12,17,22,25). Despite the greater in vitro activity of ciprofloxacin against P. aeruginosa isolates and the Enterobacteriaceae, levofloxacin has proved to be more effective than ciprofloxacin in treating experimental infections in rats in one study (16).…”
Section: Methodssupporting
confidence: 91%
“…When the susceptibility test results of this survey were compared with those of previous studies, there was little to no difference in the percentage of isolates of most species suscep-tible to the three quinolones. Although earlier studies indicated that nearly all staphylococci, including methicillin-resistant strains, were susceptible to these quinolones (7,8,23,28), our data are very comparable to those from more recent reports indicating the greatly reduced susceptibilities of methicillin-resistant strains (6,29). Enterococci could not be adequately evaluated because nearly half of the isolates were not identified to the species level.…”
Section: Methodssupporting
confidence: 50%
“…The majority of quinolone-resistant mutants selected by exposure to ofloxacin simultaneously lose the ability to produce coagulase, and they may be less virulent than ciprofloxacin-selected mutants (42). Similarly, quinolone-resistant mutants of coagulase-negative staphylococci selected by exposure to levofloxacin, which is the optically active isomer of ofloxacin, exhibit higher 50% lethal doses than the parent strain in a murine model of systemic infection, suggesting a reduction of strain virulence coincident with the development of resistance (13). In our model, however, the quinoloneresistant strain 5252 had an ID50 of only 9 CFU among guinea pigs receiving placebo, suggesting that it can establish infection as readily as the quinolone-susceptible strains of S. aureus and S. epidernidis can.…”
Section: Resultsmentioning
confidence: 99%
“…Over 98% of all isolates were suscep tible to =¿16 pg/ml ofloxacin in contrast to ci profloxacin where over 50% of MRSA isolates were resistant to 32 pg/ml of the drug. Com bining this information with the low rate of spontaneous mutations reported for staphylo cocci leading to resistance to ofloxacin [7][8][9], and the 2-to 4-fold increased in vitro activity of/-ofloxacin compared to ofloxacin [10,11] in dicates that further evaluation of the optically active isomer of ofloxacin as a treatment, ei ther alone or as part of combination therapy, for multidrug-resistant S. aureus is warranted. Evaluation of potential agents such as this is of some medical urgency due to the recent report of in vitro tranfer of vancomycin resistance to MICS are given in pg/ml.…”
Section: Discussionmentioning
confidence: 95%
“…Staphylo coccal resistance to virtually all antimicrobial agents, including the new glycopeptide and lipopeptide compounds, has either appeared clinically or been selected in vitro [3]. Interest in the potential use of newer fluoroquinolones for treatment of infections due to methicillinrcsistant staphylococci has diminished due to the emergence of many isolates no longer fully susceptible to these agents [4,5], However, there appears to be both a difference between the inherent activity of various fluoroquino lones against staphylococci, and a difference in the frequency at which resistance-associ ated spontaneous mutations occur with re spect to specific quinolone agents [4][5][6][7][8], One of the lowest spontaneous mutation rates for ciprofloxacin-susceptible staphylococci has been associated with ofloxacin [7,8], and mu tants are 16-to 32-fold less resistant to ofloxa cin and /-ofloxacin than to ciprofloxacin [9], The optically active form of ofloxacin, /-oflox acin (DR-3355, lcvofloxacin) appears to be 2-to 4-fold more active against staphylococci than racemic ofloxacin [10,11], and has been reported to remain active (MIC90 = 3.13 pg/ ml) against ciprofloxacin-resistant (MIC. *) = 25 pg/ml) MRSA [11].…”
Section: Introductionmentioning
confidence: 99%